How Customer Satisfaction Affects Employee Satisfaction and Retention in a Professional Services Context. (November 2013) - Frey, Regina-Viola; Bayón, Tomás; Totzek, Dirk
While retention of highly qualified employees is vital for professional services firms, prior research has largely neglected the role of customers as a driver of employee satisfaction and retention. Drawing on an experimental study and a dyadic field study, this article shows that client satisfaction is an important determinant of employee satisfaction, which in turn increases employee retention. Thus, for professional services firms, the common logic in relationship marketing that employee satisfaction affects client satisfaction can also be reversed. First, in line with balance theory, an attitudinal transfer occurs from the client to the employee which is stronger when both share the same opinion about their collaboration. Second, in line with Herzberg's motivational theory, client satisfaction indirectly affects employee satisfaction by affecting the perceived appreciation the employee receives from the customer. These findings have three major managerial implications: First, investments into client satisfaction might pay off double by enhancing revenues and profit on one hand, and enhancing employee satisfaction and retention, on the other hand. Second, positive client feedback has positive effects on employee satisfaction and recognition. Third, these results suggest that marketing and human resource issues are intertwined in professional services firms. Thus, service firms should encourage ample communication and collaboration between these functions.